Restorative Justice for Victims of Terrorism: Healing Beyond Retribution - Barus, Faby Izaura Y; Priyanto, Sapto; Syauqillah, Muhamad (International Journal of Social Service and Research, 2023)
This research investigates the application of restorative justice in Indonesia's approach to terrorism, highlighting its potential to transform traditional justice methods. It focuses on the benefits of restorative justice in empowering victims, promoting offender accountability, and enhancing community trust. The study acknowledges the challenges in implementation, including legal, security, and cultural barriers, as well as resource constraints. Proposed solutions involve legal reforms, heightened security protocols, and increased public awareness. The conclusion emphasizes that restorative justice, with its emphasis on healing and community engagement, is a crucial step towards a more inclusive and effective response to terrorism's societal impacts in Indonesia.